2016
DOI: 10.1542/peds.2016-2416
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Conditions and Medical and Surgical Hospital Utilization

Abstract: OBJECTIVE: Mental health conditions are prevalent among children hospitalized for medical conditions and surgical procedures, but little is known about their influence on hospital resource use. The objectives of this study were to examine how hospitalization characteristics vary by presence of a comorbid mental health condition and estimate the association of a comorbid mental health condition with hospital length of stay (LOS) and costs. METHODS:Using the 2012 Kids' Inpatient Database, we conducted a retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 47 publications
(11 reference statements)
2
34
0
Order By: Relevance
“…Longer length of stay may be one reason for this finding. Doupnik et al 32 found that mood disorders tended to be more strongly associated with a longer pediatric length of stay for common medical and surgical admissions than with ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Longer length of stay may be one reason for this finding. Doupnik et al 32 found that mood disorders tended to be more strongly associated with a longer pediatric length of stay for common medical and surgical admissions than with ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…5 -8 Hospitalizations among pediatric patients with comorbid mental health diagnoses increased in children's hospitals by 160% from 2005 to 2014, 6 with comorbid mental health diagnoses leading to increased length of stay and cost. 8 In recognition of this burden, recent federal health policies have identified pediatric mental health care as a key target area for quality measurement and improvement. 9,10 In March 2011, the Centers for Medicare and Medicaid Services and the Agency for Healthcare Research and Quality partnered to fund 7 Centers of Excellence that constitute the Pediatric Quality Measures Program mandated by the 2009 Child Health Insurance Program Reauthorization Act.…”
mentioning
confidence: 99%
“…29 Prior investigations have found that children with an MHC tend to stay longer in the hospital compared with children with no MHC. 32 Results from the present study suggest that children with MHCs also experience more inpatient days because of rehospitalizations. Subsequent investigations should strive to understand the mechanisms in the hospital, community, and family environment that are responsible for the increased inpatient utilization in children with MHCs.…”
Section: Discussionmentioning
confidence: 53%